From Reactive to Proactive Attitudes toward Hydropower Dams in the Mekong Region - CGIAR Challenge Program on Water and Food (2014)
In the Mekong region, increasing power demand and growing interest to capitalize on the region’s inherent hydropower potential have led to a surge in hydropower development. In 2010, more than 3,200 MW of hydropower capacity, about a tenth of the region’s total potential, had been installed on the Mekong River’s tributaries.1 Many more dams are either planned or currently under construction. While the development of hydropower is expected to have irreversible impacts on both communities and the environment, dam developers and governments often fail to consider and inform about the full costs and benefits of hydropower. As a result, communities, local government agencies, and other stakeholders remain uncertain about what to expect from planned hydropower dams.